Numerical investigation on the effect of the inlets on the performance of oil/water separation in hydro cyclone - Yin, K.Y. (Asian Research Publishing Network, 2016)
Hydro cyclone are widely used in oil and gas industry particularly in this study similar to de-oiling process or improve purification of discharged water. As offshore oil production started to decline over time with high water cut in the production stream, this usually cause unprofitable production for huge expenditures in water handling. The periodically collapse in oil price further heightened the awareness on production technology to reduce unit costs. This paper offers a comprehensive suite of numerical simulation to predict the performance of oil-water hydro cyclone in an effort to reduce amount of water production at surface. Separation performance impact from single, dual and quad inlets configuration is simulated based on a tested turbulence and multiphase model. This investigation was carried out using Computational Fluid Dynamics in ANSYS-FLUENT 14 environment. The hydro cyclone swirling flow was simulated using RNG swirl dominated k-Îµ Turbulence model while the interface between crude oil and water was achieved using the Discrete Phase model. Based on the simulation results, it is concluded that hydro cyclone separation efficiency is affected by inlet velocities at tangential inlet and number of tangential inlets. Â© 2006-2016 Asian Research Publishing Network (ARPN).